2017
DOI: 10.1097/yct.0000000000000377
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Memory Immediately Following Electroconvulsive Therapy

Abstract: OBJECTIVES The aims of the present study were to describe the short-term rate of subjective memory worsening (SMW) and identify factors of importance for SMW in a large clinical sample treated for depression with electroconvulsive therapy (ECT). METHODS This register-based study included 1212 patients from the Swedish National Quality Register for ECT. Subjective memory worsening was defined as a 2-point worsening on the memory item of the Comprehensive Psychopathological Rating Scale from before to within 1 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 33 publications
6
28
1
1
Order By: Relevance
“…Possibly CPRS-M-S is less well correlated to CPRS-M in this group. A recent study based on the Q-ECT data showed subjective memory worsening for 26% [13] compared to 20% (CPRS-M) and 27% (CRPS-M-S) in our study. Taking all this into account and bearing the limited sample size in mind, our study sample differs in some aspects from the Q-ECT and therefore does not fully represent the population in the Swedish Q-ECT.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…Possibly CPRS-M-S is less well correlated to CPRS-M in this group. A recent study based on the Q-ECT data showed subjective memory worsening for 26% [13] compared to 20% (CPRS-M) and 27% (CRPS-M-S) in our study. Taking all this into account and bearing the limited sample size in mind, our study sample differs in some aspects from the Q-ECT and therefore does not fully represent the population in the Swedish Q-ECT.…”
Section: Discussioncontrasting
confidence: 50%
“…The primary aim of this study was to analyze the consistency between self-reported and physician rated subjective memory in depressed patients before and after ECT treatment. This is important for the ability to compare self-ratings with previous reports using clinician's ratings [13]. The hypothesis of the study was that there is a high and significant consistency that supports using patients' self-reported subjective memory in clinical practice and in the Swedish Q-ECT.…”
Section: Introductionmentioning
confidence: 93%
“…According to a 17year retrospective study of 1571 ECT recipients, psychiatric individuals who received ECT had lower mortality than those who did not, though nested social and physical parameters affected the results (Liang et al, 2017), and another multistate observation study showed the effect of ECT in reducing shortterm readmission risk among those with server affective disorders (Slade et al, 2017). With respect to effects on memory, Brus et al (2017) used national register-based information to inquire about the rate of subjective memory worsening (SMW) reported with ECT, suggesting that patients who were female, young, less cognitively impaired before ECT, treatment-resistant, and experiencing wider pulse width were more likely to be subject to SMW, and their SMW reported rate was not low. However, this study had such limitations as significantly heterogeneous interference, subjective report collection, and the details of the ECT procedure.…”
Section: Clinical Observation By Questionnaire Assessmentsmentioning
confidence: 99%
“…However, cognitive decline was noted in some depressed patients who received ECT (Brus et al, 2017), and recovery from this declination was suggested to take half a year (Nuninga et al, 2018). However, whether ECT contributed more memory loss than pharmaceutical treatment is still in dispute, but the majority support the view of no additional cognitive damage ascribable to ECT than antidepressants (Husain et al, 2004;Kellner et al, 2016a,b;Bjoerke-Bertheussen et al, 2018).…”
Section: Safety and Effectiveness Of Ectmentioning
confidence: 99%
See 1 more Smart Citation